Sub-prosthetic injuries in patients carrying total denture - Vilchez Salazar, Ernesto (2013)
The purpose of this study was to determine the injuries that occur in soft tissue support in patients carrying total denture attended at dental clinic of San Marcos University in 2012. There were 40 evaluated patients between 53 and 86 years old, previous calibration. In order to determine the changes into the mucosa of support, all patients underwent a cytological smear. Each sample was stained with the Papanicolaou technique and performed with Bethesda system. The results indicated that 95 % had mucosal lesions, of which 10 % had dysplasia cells, 7.5% leukoplakia stomatitis 55 %, 17.5 % hyperplasia, 5 % ulcer. The 90 % of the prostheses presented instability. No significant difference was observed in the different occlusal schemes. Therefore, we concluded that the majority of patients with unstable prosthesis have developed sub-prosthetic injuries; therefore we emphasize that the prosthesis over one year of use should have a regular monitoring by the specialist, avoiding malignant lesions.